Power and progress : our thousand-year struggle over technology and prosperity - Acemoglu, Daron; Johnson, Simon (New York: Public Affairs, 2023)
"Two bestselling authors overturn conventional wisdom about how economies work, revealing the untold story of who wins and who loses the rewards of prosperity, in a work that fundamentally transforms how we look at and understand the world"--
Includes bibliographical references (pages 475-516) and index.
Keywords: Technology -- Social aspects; Technology -- Economic aspects; Progress